Strategi efektif pencegahan nyeri saraf kejepit melalui gerakan senam yoga - Sulaiman, Sulaiman (Journal of Pharmaceutical and Sciences, 2023)
Pinched nerve pain is a prevalent ailment among the populace of Indonesia. Many endured adversity between the ages of 30 and 45. In general, males exhibit a higher prevalence rate. Pain in the belly, groyne, and limbs is something that people who are impacted by this nerve will describe as being present. This study aimed to determine whether or not regular yoga acrobatics could alleviate nerve pain in patients suffering from nerve pain. Semi-experimental methods are employed in this study. Nerve pain affected sixty individuals who comprised the population of this study. Utilising purpose sampling as a sampling method. Regular yoga and gymnastics participation reduces nerve pain by 66.33 percent, in accordance with the results of this research. According to the findings of this study, participating in regular yoga practice results in a substantial reduction in nerve closures (p = 0.000).